Penerapan IPTEK pada Tanaman Kalakai untuk Meningkatkan Kesehatan di Posyandu Desa Sungai Besar, Kabupaten Banjar: Application of Science and Technology on Kalakai Plants to Improve Health at the Sungai Besar Posyandu, Banjar District - Wati, Helmina; Afra, Fairuz Yaumil; Adhipurna, Novian; As-Syahri, Hidayatullah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Nutritional problems among toddlers in South Kalimantan, particularly stunting, remain a pressing public health issue. Sungai Besar Village, Banjar District, faces a high prevalence of stunting despite its abundant natural resources, including the nutrient-rich kalakai plant. This community service program aimed to promote the utilization of kalakai as a strategy to prevent stunting and improve community health. The program involved an initial survey, interviews with posyandu cadres, health education on iron and folic acid supplementation, and training in processing kalakai into nutritious food products such as kalakai syrup. Evaluation was conducted through pre- and post-test questionnaires to measure knowledge improvement among posyandu cadres. The program attracted strong community participation, involving 65 participants, and demonstrated a significant increase in cadres’ knowledge and skills, reaching 98% after the intervention. Furthermore, processing kalakai into value-added products created new economic opportunities for the community. Thus, the application of science and technology to kalakai utilization proved effective in improving health and reducing stunting prevalence in Sungai Besar Village.